Geographical Maldistribution of Native Hawaiian and Other Pacific Islander Physicians in Hawai‘i - Ambrose, Adrian Jacques H (University Clinical, Education & Research Associate (UCERA), 2012)
BACKGROUND: Native Hawaiians and other Pacific Islanders (NHOPI) have high prevalence of overweight status, obesity, and hypertension, as well as high rates of asthma and cancer mortality. Some barriers to health care delivery for this population are a physician shortage in Hawai‘i and a geographical maldistribution of actively practicing physicians. This study examines the distribution of NHOPI physicians compared to the NHOPI population in Hawai‘i through Geographical Information System choropleth mapping. METHODS: The maps and results were gathered and constructed from Census Tract data from the US Department of Commerce, the Census Bureau, the Physician Workforce Assessment, and the ‘Ahahui o nā Kauka reports. RESULTS: With the exception of East Honolulu, all areas of Hawai‘i show drastic disparities in the ratio of NHOPI physicians to NHOPI populations as compared to the ratio of total physicians to the total population. DISCUSSION: Given the NHOPI physician shortage and their geographical maldistribution, this study underscores the importance of increasing the number of NHOPI medical school applicants, graduates, residents, and physicians in permanent active practices in rural areas and the neighbor islands. Current institutional and academic programs, such as the John A. Burns School of Medicine, Imi Ho‘ola, and the Native Hawaiian Center of Excellence, are contributing to resolving some of the health disparities and should consider expanding their efforts.